Physiological constraints and comparative economic development - Carl-Johan Dalgaard; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
It is a well known fact that economic development and distance to the equator are positively correlated variables in the world today. It is perhaps less well known that as recently as 1500 C.E. it was the other way around. The present paper provides a theory of why the 'latitude gradient' seemingly changed sign in the course of the last half millennium. In particular, we develop a dynamic model of economic and physiological development in which households decide upon the number and nutrition of their offspring. In this setting we demonstrate that relatively high metabolic costs of fertility, which may have emerged due to positive selection towards greater cold tolerance in locations away from the equator, would work to stifle economic development during pre-industrial times, yet allow for an early onset of sustained growth. As a result, the theory suggests a reversal of fortune whereby economic activity gradually shifts away from the equator in the process of long-term economic development.
Keywords: O11; I12; J13; 330; long-run growth; evolution; nutrition; fertility; education; comparative development